Peran Peradi terhadap Advokat yang Melakukan Pelanggaran Kode Etik Profesi Advokat - Wandira A, Irham; Suheri, Muhammad; Zahara, Fatimah; Lubis, Fauziah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Advocate profession is closely related to advocate organizations as a forum for advocates. Advocate profession is an honorable profession (officium nobile) because it devotes itself to the interests of society, not only for personal gain. One of the roles of an advocate is as a supervisor and guardian of justice. However, when viewed from the implementation and enforcement so far, it is often seen that the advocate's code of ethics is a complement that most advocates pay little attention to. Violations of the code of ethics are often committed by advocates in carrying out their profession and do not even hesitate to carry out these actions openly. If there is a violation of the Code of Ethics, the Advocate Honorary Council has the right to impose sanctions and decide to impose sanctions in accordance with the articles stipulated in the Indonesian Advocate Code of Ethics contained in Article 7 paragraph (1) of the Law on the Indonesian Advocate Code of Ethics. This research is a normative legal research group, namely legal research that uses a type of doctrinal research or also called normative juridical research (legal study research). Keywords: Advocate, Code of Ethics, Peradi.